Incidence, management and prognosis of new-onset sarcoidosis post COVID-19 infection - Vij, Oliver; Dey, Mrinalini; Morrison, Kirsty; Kouranloo, Koushan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: SARS-CoV-2 infection has been linked to hyperinflammation in multiple organs with a potential mechanistic link with resulting autoimmunity. There have been reports of many inflammatory complications following COVID-19, including sarcoidosis. A literature review on new-onset sarcoidosis following COVID-19 is lacking. We evaluated potential associations between COVID-19 and development of new-onset sarcoidosis. Methods: Articles discussing biopsy-proven sarcoidosis after confirmed COVID-19 infection, published 1956 until April 2023, were included. All article types were deemed eligible except opinion and review articles. Results: A pooled total of 15 patients with new-onset diagnosis of sarcoidosis after COVID-19 infection were included, 45.5% female, mean age 46.1 years (standard deviation 14.7) at onset of sarcoidosis. Patients were from: Europe (n=11); North America (n=2); South America (n=1); Asia (n=1). The mean time between COVID-19 infection and diagnosis of sarcoidosis was 56.3 days, although this ranged from 10 to 140 days. Organ systems predominantly affected by sarcoidosis were: pulmonary (n=11); cutaneous (n=3); cardiac (n=2); ocular (n=1); systemic (n=1) (with overlapping features in certain patients). Sarcoidosis was treated as follows: glucocorticoids (n=8); azathioprine (n=1); cardiac re-synchronisation therapy (n=1); heart transplant (n=1). All patients were reported to have survived, with one requiring intensive care admission. Conclusions: Our result suggests there is a potential link between COVID-19 and new-onset sarcoidosis. The potential mechanism for this is through cytokine mediated immune modulation in COVID-19 infection. Obtaining a tissue sample remains key in confirming the diagnosis of sarcoidosis and this may be delayed during active COVID-19 infection.